2019
DOI: 10.14260/jemds/2019/611
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment and its Correlates in Chronic Kidney Disease Patients Undergoing Haemodialysis

Abstract: BACKGROUND Cognitive Impairment (CI) has been found to be quite common amongst patients with Chronic Kidney Disease (CKD) undergoing haemodialysis (HD). The presence of these deficits could affect patient’s adherence to diet regimens, treatment and also reduce their Quality of Life. The presence of depression in such patients can further lead to CI. We wanted to assess the prevalence of CI in CKD patients undergoing haemodialysis, socio-demographic and patient related variables affecting CI, and also the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 22 publications
4
20
0
Order By: Relevance
“…Lower levels of education are associated with cognitive impairment in our study, as reported by others [32,35,36]. This may be explained by the association of lower education levels with poor functional and cognitive reserves.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Lower levels of education are associated with cognitive impairment in our study, as reported by others [32,35,36]. This may be explained by the association of lower education levels with poor functional and cognitive reserves.…”
Section: Discussionsupporting
confidence: 89%
“…To evaluate the frequency of depression and its effect on cognitive performance, the Geriatric depression scale (GDS) was adopted, and in our study depression was found to be significantly associated with cognitive impairment. Other studies have also found similar decline in cognition with the presence of depression [32,38,39]. This can be explained by the effects of symptoms of depression on domains of executive functioning and processing speed, in keeping with previous studies [39].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…20 Those chronic kidney disease patients with cognitive impairment have an increased risk of death, poor quality of life, difficulty in adhering to medications, and worse quality of emotional well-being. [21][22][23][24][25][26][27][28][29] It is a major cause of morbidity and a determinant of the quality of life in the elderly chronic kidney disease patients. 30,31 Among hemodialysis patients it is also associated with an approximately two-fold increased risk of both mortality and dialysis withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…Kurella, Chertow, Luan, and Yaffe (2004) reported that the incidence of cognitive impairment is approximately 2 to 7 times higher among ESRD patients than among other patients (Kurella et al, 2004). All of the above studies emphasized the importance of research into the relationship between ESRD and cognitive impairment (Cerasola, Nardi, Palermo, Mulè, & Cottone, 2011; Fukunishi et al, 2002; Joseph, Bhandari, & Dutta, 2019; Owolabi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%